Pendampingan Digitalisasi Pemasaran UMKM melalui Pemanfaatan E-Commerce di Desa Bumi Nabung Utara, Lampung Tengah - Ronal Jusuphan Maulana; Muhammad Ma’ruf; Suci Salsabila; Sukma Kumala Sari; Venny Aprilia; Vivi May Saputri; Windi Elviana; Yulita Dian Andini; Olyfiah Nazzwa Saputri; Alfiansyah Imanda Putra (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2026)
The rapid development of digital technology has created opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand their market reach; however, low digital literacy and the continued dominance of conventional marketing remain major challenges, particularly in Bumi Nabung Utara Village. This Community Service Program (PKM) aims to enhance digital literacy and marketing capabilities of MSME actors through the utilization of e-commerce and social media. The method employed is Participatory Action Research (PAR), which includes stages of observation, socialization, training, and practical assistance. The program partners are MSME actors engaged in handicrafts and traditional food businesses, specifically tiwul, with success indicators including the ability to create and manage promotional accounts and produce simple digital content. The results show that participants are able to use platforms such as Facebook and TikTok Shop for promotion and create marketing content. In addition, business banners were developed to strengthen product identity. The impact of this program includes improved digital understanding and skills among MSME actors, expanded marketing reach, and increased business competitiveness. Furthermore, the program encourages the sustainable use of digital technology in business development.